Intense red emission via energy transfer from (Ce3+/Eu3+):P2O5+NaF+CaF2+AlF3 glasses for warm light sources - P. Meejitpaisan (2020)
© 2020 Elsevier Ltd and Techna Group S.r.l. Europium (Eu3+)-doped fluorophosphate (PNCA:P2O5+NaF + CaF2+AlF3) glasses with the addition of cerium (Ce3+) ions were fabricated by the melt-quenching technique to know their ability for the bright red (615 nm) luminescence. The emission (PL) and excitation (PLE) spectra, decay curve measurements as well as energy transfer (ET) process of Ce3+→ Eu3+ were studied in detail. An excitation spectrum related to the 7F0→ 5D2 level of Eu3+ is used to estimate the phonon energy (1121 cm−1) of the title glass host. Under ultraviolet (UV) irradiation of 299 nm, the PL spectra of (Ce3+/Eu3+):PNCA glasses show intense red emission at 615 nm whereas the lifetime decrease with respect to increase of Eu3+ that could support the observed efficient ET from Ce3+ to Eu3+. The ET:Ce3+ →Eu3+ via quadrupole-quadrupole process was confirmed by Reisfeld's approximation and Dexter's ET formula. The ET efficiency (ηET) and critical distance (Rc) were also calculated. Interestingly, the (Ce3+/Eu3+):PNCA glasses showed intense red light emission with low correlated color temperatures and the corresponding color purity reached as great as 99%, indicating its potentiality as a red component for warm light sources.